Cutaneous leiomyosarcoma with osteoid metaplasia in a budgerigar (Melopsittacus undulatus): a case report - Timurkaan, N.; Eroksuz, H.; Cevik, A.; Karabulut, B. (Czech Academy Agricultural Sciences, 2016)
Cutaneous leiomyosarcoma with osteoid metaplasia was diagnosed at the base of the right wing in a five-year-old female budgerigar. Grossly, the tumour mass was well circumscribed and solitary, and had a nodular appearance on section. On histological examination, the mass was composed of randomly arranged bundles of spindle-shaped cells that included mitotic, multi-nucleated and bizarre cells. In addition, within and between tumour areas, there were osteoid metaplasia foci. The bony trabeculae were usually localised in the areas around the haemorrhage, and exhibited focal mineralisation. Tumour cells were stained red using Masson's trichrome staining method. In addition, tumour cells were intensively positive for smooth muscle actin and focally positive for desmin and vimentin, but were negative for CD68 and S100 by immunohistochemical staining. The tumour reported here was defined as a cutaneous leiomyosarcoma with osteoid metaplasia by histopathological and immunohistochemical findings. Our findings may indicate that osteoid metaplasia should be considered in leiomyosarcoma in budgerigars.
Keywords: desmin; CD68; smooth muscle actin; spindle-shaped cells; S100